Training Strategy and Employee’s Performance: Lessons from Kenya Power - Kalei, Anne; Jamleck, Denis Muchangi; Kasimu, Josephine Katunge; Lewa, Susan Katinda (International Journal of Science and Engineering, 2015)
The study sought to examine the relationship between training strategy and employees’ performance at Kenya Power. The study was motivated by concerns on employee performance in the organization despite the consistent training practices that the organization undertakes to enhance employee performance. Descriptive research design followed by a quantitative approach was used. The target population was 300 employees drawn from energy transmission division of Kenya power. Using stratified sampling, the researcher selected 100 respondents who formed the study’s sample size. Primary data was collected through self-administered questionnaires’ while secondary data was obtained from KP’s official reports, journals and empirical studies linking training strategy and employee performance. A pilot study was undertaken to determine the validity and reliability of the research instruments. Data was analyzed using both descriptive and inferential statistics. The study findings indicated that there is a general acceptance that choosing an appropriate training strategy based on set performance standards of an organization has an overall influence on the performance of employees. The study recommended a need for organization to either re-examine the deficits in the training strategies in order to establish why maximum employee performance is not realized through training alone.
Keywords: Training; Strategy; Employee; Performance; Motivation; Morale; Self-satisfaction; Relationship.